Cocaine-induced behavioral sensitization in adolescent rats endures until adulthood: Lack of association with GluR1 and NR1 glutamate receptor subunits and tyrosine hydroxylase - Marin, Marcelo Tadeu [UNESP]; Cruz, Fabio C.; Planeta, Cleopatra da Silva [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Exposure to repeated cocaine induces enduring behavioral sensitization, which has been implicated in the psychostimulant-induced craving and psychosis. Adaptations in dopamine and glutamate neurotransmission in the nucleus accumbens (NAc) and medial prefrontal cortex (mPFC) seem to mediate psychostimulant-induced behavioral sensitization. The abuse of drugs often begins during adolescence; however few studies have been devoted to study the effects of drugs of abuse at this age. The aim of our study was to examine whether repeated cocaine during adolescence could induce behavioral sensitization that endures into adulthood. Moreover, the protein levels of Tyrosine Hydroxylase (TH) and the glutamate receptor subunits GluR1 and NR1 in the NAc and mPFC were measured following the behavioral tests. Adolescent rats were treated with cocaine from postnatal day (PND) 30 to PND34 and behavioral sensitization was verified recording locomotor activity after cocaine challenge injection to adolescent (PND37) or adult (PND64 or 94) rats in separate groups at each time point. TH, GluR1, and NR1 protein levels were measured by Western blotting. Rats exposed to cocaine during adolescence expressed behavioral sensitization when tested on PND37 and PND64. In cocaine sensitized rats GluR1 protein was increased in the mPFC on PND37 but not in other ages. Thus, cocaine-induced behavioral sensitization during adolescence endures into early adulthood. However, cocaine pretreatment during adolescence induced a transient increase of GluR1 in the mPFC only when animals were challenged in the same age. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: behavioral sensitization; cocaine; adolescence; glutamate receptors; tyrosine hydroxylase